Forms of Affect, Relationality, and Periodical Encounters, or ‘Pine-Apple for the Million’ - Jasper Schelstraete (Journal of European Periodical Studies, 2016)
The social, economic, intellectual, cultural, and material relations that comprise periodical encounters have been attended to in analyses that invoke the concept of the network, what Nathan Hensley has described as a ‘chain of visible or material interactions among human and nonhuman entities’. The affective dimensions of these relations, however, are neither material nor always visible, yet they are fundamental to all such interactions. This article argues that the periodical’s capacity to communicate, the contours, scope, and effects of that capacity, and in particular its genre traction, are everywhere underscored by a relationality that is charged with affect and emotions, shaped by what Raymond Williams famously described as ‘structures of feeling’. My focus on the haptic currents that drive periodical exchanges (taking examples from George Eliot at the Cornhill Magazine, Joseph Conrad in Blackwood’s Edinburgh Magazine, and James Joyce in the Irish Homestead) follows from important theorizations of the unique affordances of this ‘most time-oriented of print forms’ (Beetham). Affect, feelings, and emotive responses are messy and cannot be pressed into a discrete methodology, but when considering the open-ended, multi-textured, serial form that is the periodical, there is something to be gained, I suggest, from trying to understand the operations of affect, its openness, its aleatoric potential, and its emotion-based effects.